(untitled) (Global Journal of Human-Social Science, 2023)
The international protagonist of the Amazon has gained ground in Brazil s foreign policy and the rate of deforestation in the region is one of the indicators of this importance Due to the current focus on the Amazon the federal government needs to justify the increase in deforestation and present plans to reduce these rates Realizing the need to better understand the topic this paper aims to analyze the foreign policy actions developed for the Amazon in the Lula 2003-2010 and Bolsonaro 2019-2022 governments focusing on forest management considering the beginning of historical monitoring in 1988 made by the Amazon Deforestation Monitoring Program In addition the discussion also contemplates Brazil s performance within the Paris Agreement and the 2030 Agenda The results of this survey show that the lowest continuous rates of deforestation occurred between 2005 and 2011 while the highest deforestation rates were registered between 2019 to 2021